1995
DOI: 10.1182/blood.v86.4.1408.bloodjournal8641408
|View full text |Cite
|
Sign up to set email alerts
|

Direct demonstration of cytokine synthesis heterogeneity among human memory/effector T cells by flow cytometry

Abstract: The array of cytokines produced by T cells in effector sites is a primary means by which these cells mediate host defense. It is well recognized that cloned T cells are heterogeneous with regard to cytokine synthesis and, thus, in their ability to mediate specific immune responses, but the extent to which the patterns of cytokine secretion observed in cloned cells reflect actual populations of memory/effector T cells existing in vivo is largely unknown. Here, we report our findings using a multiparameter flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
175
0
3

Year Published

1998
1998
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 495 publications
(198 citation statements)
references
References 37 publications
20
175
0
3
Order By: Relevance
“…Jung et al [17] also showed that freshly isolated unstimulated blood lymphocytes do not produce IFN-g, IL2 or IL4 cytokines as measured by intracellular staining or mRNA analysis. Similar to data from Picker et al [2], a 4-h incubation with PMA/I at 37°C was optimal for intracellular cytokine expression (data not shown). Furthermore, while PMA/I does reduce the fluorescence intensity of anti-CD4 staining [2], the percentage of CD4 positive helper T cells was not significantly different between unstimulated and stimulated samples (n = 26, mean ± s.e.m.…”
Section: Intracellular T Cell Cytokine Methods Validationsupporting
confidence: 87%
See 3 more Smart Citations
“…Jung et al [17] also showed that freshly isolated unstimulated blood lymphocytes do not produce IFN-g, IL2 or IL4 cytokines as measured by intracellular staining or mRNA analysis. Similar to data from Picker et al [2], a 4-h incubation with PMA/I at 37°C was optimal for intracellular cytokine expression (data not shown). Furthermore, while PMA/I does reduce the fluorescence intensity of anti-CD4 staining [2], the percentage of CD4 positive helper T cells was not significantly different between unstimulated and stimulated samples (n = 26, mean ± s.e.m.…”
Section: Intracellular T Cell Cytokine Methods Validationsupporting
confidence: 87%
“…Validation criteria are reported on PMA/I stimulated blood samples because cytokine levels in unstimulated T cells were below the limit of sensitivity of the assay (≥1 cell in 10 000) as reported previously [2,9]. Jung et al [17] also showed that freshly isolated unstimulated blood lymphocytes do not produce IFN-g, IL2 or IL4 cytokines as measured by intracellular staining or mRNA analysis.…”
Section: Intracellular T Cell Cytokine Methods Validationmentioning
confidence: 92%
See 2 more Smart Citations
“…CD4 + or CD8 + T cells was performed as described. 20) Briefly, the patient's CD4 + or CD8 + T cells were continuously treated with FACS lysing and permeabilization solutions (Becton Dickinson Immunocytometry System; San Jose, CA). The cells were subsequently incubated with FITC-anti-IFN-γ (Becton Dickinson) and PE-anti-IL-4 (Becton Dickinson) in 0.1% BSA-PBS; FITC-mouse IgG2a and PE-mouse IgG1 (Becton Dickinson) were used as controls.…”
Section: Reverse Transcriptase-polymerase Chain Reaction (Rt-pcr) Anamentioning
confidence: 99%